The Psychosocial Aspect of Neet Young People - Stevanović, Aleksandar M.; Martínez, Almudena Iniesta; Sánchez, Práxedes Muñoz (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Youth is a critical developmental period characterised by the transformation from childhood into adulthood, that is, the maturation of the psychological apparatus and psychosocial functioning from an infantile to an adult state. Most young people navigate this phase successfully; however, some experience noticeable changes in behaviour and psychosocial functioning. These psychological transformations, occurring over a relatively short period and affecting all aspects of personality, can potentially lead to a disorganisation of the young person’s being. For this reason, youth can represent a risky period that can cause psychological problems and specific psychopathologies, both in terms of manifestation and psychodynamics. NEET youth, as a particularly sensitive group, face increasing mental health challenges. The aim of this paper is to examine the psychosocial aspects of NEET youth to inform preventive measures and interventions.
Keywords: NEET; mental health; depression; motivation; social exclusion